Bacterial cellulose nanofibers for separation, drug delivery, wound dressing, and tissue engineering applications - Tamahkar, Emel; Topçu, Aykut Arif; Perçin Demirçelik, Işık; Aslıyüce, Sevgi; Denizli, Adil (Elsevier, 2022)
Bacterial cellulose (BC) nanofibers with high purity, high surface/volume ratio, high biocompatibility, high porosity, high tensile strength, and high water holding capacity are emerging attractive biomaterial. BC nanofibers can be prepared simply via bacterial incubation withalow cost inadetermined shape owing to its in-situ moldability. BC nanofibers due to its structural and morphological properties have demonstrated great potential asanative form or with various modifications using polymers, micro/nanoparticles, and small molecules for diverse application areas. This review aims to discuss the applicability and efficiency of the BC nanofibers and its composites focusing on the unique characteristics of BC in the fields of separation, drug delivery, wound dressing, and tissue engineering. It overviews the recent developments about the fabrication methods of BC that was used asaseparation medium, adrug delivery vehicle, awound dressing material, andascaffold. © 2022 Elsevier Inc. All rights reserved.
Keywords: Bacterial cellulose nanofibers; drug delivery; separation medium; tissue engineering; wound dressing